Tree Growth And Financial Evaluation of Agroforestry System in Kampung Tebuk Pulai, Sabak Bernam, Selangor - Joseph Sikul, Julsun (2005)
A study was conducted at Kg. Tebuk Pulai, Sabak Bernam, Selangor to assess the growth performance and financial aspects, evaluate the financial component and also to determine the optimum combination of agroforestry system practised by the farmers. There are three farms involved in the study with the holding size of two hectares each. The farms were planted with teak trees as the major component and practised different types of agroforestry system. This study involved collection of data on growth of teak and Tongkat Ali and other information obtained through informal interviews with the farmers. The results of this study are explained in terms of assessment on growth performance and financial aspects of three different agroforestry systems, evaluation of financial component and also determination of the optimum combination of agroforestry system. In terms of growth performance, the diameter and height growth of teak trees in the three farms are significantly different (P 5 0.05). Trees in Farm C performed the best followed by trees in Farms A and B. Farms A and €3 had a total of 11 22 and 21 73 teak trees, respectively and most of the trees are in the diameter class ranging from 12-14cm for both farms. For Farm C, a total of 1651 teak trees were recorded and most of them occurred in the diameter class range of 14-1 6cm. The total volume projected in Farms A, B and C is 11 1 .9m3/ha, 92.2m3/ha, 1 20.6m3/ha with the mean growth of 1 7.4m, 16.4m and 20.0m, respectively. Similarly, the basal diameter and height of Tongkat Ali seedlings in Farm C were significantly higher (P I 0.05) than those in Farm B. Farms B and C had 1522 and 1976 Tongkat Ali seedlings, respectively. Most of the seedlings in Farm B are in the basal diameter class range of 1.1-2.0cm with a total of 276.80kg of root weight and in Farm C most of the seedlings are in the basal diameter class range of 3.1 -4.Ocm with a root weight of 783.ZOkg. The project financial appraisal as "Type B With Project Approach" of Farm C was projected as the most economically viable project among the three farms giving the highest return to the farmer. The agroforestry system introduced under agrosilvopastoral in this farm (Scenario Ill) shows the IRR, NPV and B/C Ratio of 34.5%, RMl50,100.91 and 1.12, respectively. If the project implemented as "Without Project Approach" and "Type A With Project Approach", Farm C is still the most economically viable project. Although, the project implemented in Farms A and B offers another option, they are still considered economically viable to be implemented as the results are acceptable for project analysis requirement. Under Scenario I, Farm A shows the IRR, NPV and BIC Ratio of 19.9%, RM27,648.05 and 3.08, while Farm B has 23.696, RM32,469.12 and 4.05, respectively. The farmers of Farms A and B will maximize the return at a 15-year rotation and the value are decreasing with the increases in the number of years.